2021
DOI: 10.1016/j.ejmp.2021.01.075
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the MC-GPU Monte Carlo code against the PENELOPE/penEasy code system and benchmarking against experimental conditions for typical radiation qualities and setups in interventional radiology and cardiology

Abstract: Introduction: Interventional procedures are associated with potentially high radiation doses to the skin. º Monte Carlo codes of radiation transport are considered to be one of the most reliable tools available to assess doses. However, they are usually too time consuming for use in clinical practice. This work presents the validation of the fast Monte Carlo code MC-GPU for application in interventional radiology. Methodologies: MC-GPU calculations were compared against the well-validated Monte Carlo simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The X-ray interaction models and material properties have been adapted from PENELOPE [12]. The code was first developed by Badal et al 2009 [7], but, as has been already highlighted, it was upgraded and validated as described in a previous article [8].…”
Section: Pymcgpu-irmentioning
confidence: 99%
See 2 more Smart Citations
“…The X-ray interaction models and material properties have been adapted from PENELOPE [12]. The code was first developed by Badal et al 2009 [7], but, as has been already highlighted, it was upgraded and validated as described in a previous article [8].…”
Section: Pymcgpu-irmentioning
confidence: 99%
“…In a recently published paper MC-GPU was validated against the well-known PENELOPE/PenEasy code system and against experimental conditions for typical radiation qualities and set-ups in IR [8]. The results showed that MC-GPU is capable of simulating the underlying physical phenomena involved in IR procedures and also of calculating the doses in different tissues and organs in very short computation times (less than one minute per irradiation event).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MC‐GPU has already been employed for simulating some applications involving low‐energy (X‐ray) beams, for example, breast imaging studies and virtual clinical trials 10,11 and coherent X‐ray scattering 12 by adapting the code to include molecular interference 13 . Original and modified MC‐GPU codes were also validated for applications in interventional radiology and cardiology 14,15 . MC‐GPU was also adapted for patient‐specific CT dose calculations 16 .…”
Section: Introductionmentioning
confidence: 99%